Fortune-telling Predictions in the Light of Faith and Reason. Religious Aspects of Informacya matematyczna by Wojciech Bystrzonowski - Raubo, Grzegorz (Tematy i Konteksty, 2021)
This article is focused on the criticism of the prophecies presented by Wojciech Bystrzonowski, an encyclopaedist and populariser of science, in his work Informacya matematyczna [Mathematical Information] (1743, 1749). The author discusses prophecies of sorcerers, physiognomy, palmistry, prophetic dreams and astrological predictions. He examines the cases of magical practices combined with religious beliefs, which he regards as dangerous manifestations of superstition. He also demonstrates that fortune-telling cannot be compatible with faith or the fundamental principles of rational reasoning. Furthermore, he emphasizes that for a critical evaluation of such predictions, the Jesuit rules for the discernment of spirits can be applied. The issues addressed in Bystrzonowski’s work are characteristic of the atmosphere of the intellectual change that took place in late Baroque and early Enlightenment.